MEDICAL VS SURGICAL TREATMENT FOR SYMPTOMATIC ENLARGED INFERIOR TURBINATE: A COMPARATIVE STUDY - Rehman, Habib -Ur-; Wahid, Fazal -I-; Zada, Bakht; Javaid, Muhammad; Haq, Naseem Ul (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the nasal patency after reducing the size of hypertrophied inferior turbinate with medication and surgery.Study Design: Prospective comparative study.Place and Duration of Study: Department of Ear, Nose, Throat, Head and Neck Surgery, Medical Teaching Institute, Lady Reading Hospital, Peshawar Pakistan, from Jan to Dec 2019.Methodology: This study was conducted at the After-sample size calculation using an online sample size calculator (OpenEpi) and after obtaining informed consent patients were divided into two groups. Patients in group A were put on medicine only and in group B surgery was conducted to reduce the size of hypertrophied inferior turbinate. Data were analyzed using SPSS version 25 and p